2023
DOI: 10.31219/osf.io/mf6j2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Behavioral Intention and Actual Use of Mobile Learning During the COVID-19 Pandemic in the Higher Education System

Abstract: ThisstudyaimstoinvestigatetheimpactonBehavioralIntentionand Actual use of Mobile Learning in the Higher Education (HE). The survey was con- ducted at Cihan University Erbil, and the data was collected by questionnaire. 207 valid questionnaires have been analyzed by Structural equation modelling (SEM). The results indicated that performance expectancy, Effort Expectancy, Facilitating Conditions, Hedonic Motivation, and Habit had a positive and significant impact on Behavioral Intention to use Mobile learning am… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…So far, empirical investigations about the impact of habits on learners' intention to utilize MALL have been scarce. However, many studies have confirmed that habits significantly influence learners' behavioral intention to engage with mobile learning (Yang et al, 2022;Zacharis and Nikolopoulou, 2022;Jameel et al, 2023).…”
Section: Mobile Assisted Language Learning (Mall)mentioning
confidence: 99%
“…So far, empirical investigations about the impact of habits on learners' intention to utilize MALL have been scarce. However, many studies have confirmed that habits significantly influence learners' behavioral intention to engage with mobile learning (Yang et al, 2022;Zacharis and Nikolopoulou, 2022;Jameel et al, 2023).…”
Section: Mobile Assisted Language Learning (Mall)mentioning
confidence: 99%